Penerapan Asas Itikad Baik Dalam Pelaksanaan Perjanjian Jual Beli Tanah - Ahmad Riansyah; Roihan; Riski Rahmadhan; M. Willy Pratama; Ricky Nopriyadi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2022)
The principles of faith in civil law must apply to any agreement, whether between individuals and individuals or between individuals with legal bodies. In paragraph 3 of article 1338 of the Covenant, referred to in this document as the